In vivo evidence for an interplay of FGF23/Klotho/PTH axis on the phosphate handling in renal proximal tubules - Ide, Noriko (Am J Physiol Renal Physiol, 2018)
Phosphate homeostasis is primarily maintained in the renal proximal tubules, where the expression of sodium/phosphate cotransporters (Npt2a and Npt2c) is modified by the endocrine actions of both fibroblast growth factor 23 (FGF23) and parathyroid hormone (PTH). However, the specific contribution of each regulatory pathway in the proximal tubules has not been fully elucidated in vivo. We have previously demonstrated that proximal tubule-specific deletion of the FGF23 coreceptor Klotho results in mild hyperphosphatemia with little to no change in serum levels of FGF23, 1,25(OH)(2)D(3), and PTH. In the present study, we characterized mice in which the PTH receptor PTH1R was specifically deleted from the proximal tubules, either alone or in combination with Klotho (PT-PTH1R(−/−) and PT-PTH1R/KL(−/−), respectively). PT-PTH1R(−/−) mice showed significant increases in serum FGF23 and PTH levels, whereas serum phosphate levels were maintained in the normal range, and Npt2a and Npt2c expression in brush border membrane (BBM) did not change compared with control mice. In contrast, PT-PTH1R/KL(−/−) mice displayed hyperphosphatemia and an increased abundance of Npt2a and Npt2c in the renal BBM, along with increased circulating FGF23 levels. While serum calcium was normal, 1,25(OH)(2)D(3) levels were significantly decreased, leading to extremely high levels of PTH. Collectively, mice with a deletion of PTH1R alone in proximal tubules results in only minor changes in phosphate regulation, whereas deletion of both PTH1R and Klotho leads to a severe disturbance, including hyperphosphatemia with increased sodium/phosphate cotransporter expression in BBM. These results suggest an important interplay between the PTH/PTH1R and FGF23/Klotho pathways to affect renal phosphate handling in the proximal tubules.